Gradient release of cardiac morphogens by photo-responsive polymer micelles for gradient-mediated variation of embryoid body differentiation. Issue 26 (16th June 2017) - Gupta, Mukesh K.; Balikov, Daniel A.; Lee, Yunki; Ko, Edward; Yu, Christopher; Chun, Young Wook; Sawyer, Douglas B.; Kim, Won Shik; Sung, Hak-Joon
Abstract : Illustration of photo-gradient mediated release of retinoic acid from polymer micelles upon photo-irradiation (365 nm). Abstract : Retinoic acid (RA) is a well-known morphogen in human development. However, how an RA gradient distribution influences cardiac development remains obscure due to the lack of appropriate experimental apparatus. To address this issue, a polymeric micelle system with covalently attached RA was engineered to deliver gradient quantities of RA upon photo-irradiation. A photo-degradable polymeric nanoparticle (NP) composed of an amphiphilic methoxy(polyethylene glycol)- b -poly(ε-caprolactone)- co -poly(azido-ε-caprolactone- g-ortho nitrobenzyl retinoic ester) copolymer was synthesized, and hanging RA was covalently attached through a photo-sensitive o -nitrobenzyl (ONB) linker. The ONB linker was efficiently cleaved when exposed to a light (365 nm)-gradient, and the consequent gradient release of RA from the micelles was demonstrated. The efficacy of the photo-gradient-mediated RA release was validated across different concentrations of polymer micelles over varied irradiation periods. It was confirmed that polymer micelles demonstrated minimal cytotoxicity when exposed to mouse embryoid bodies (EBs). Finally, when the photo-gradient release of polymer micelles was applied, GFP-cardiac troponin T reporter mouse EBs demonstrated a concurrent gradient-like pattern of cardiac differentiation, verifying the utility of our novel photo-gradient approach to study morphogen gradients not only for cardiac development but also for other potential biological microenvironments subject to morphogen presentation with highly defined spatial and temporal geometries.